Design and Implementation of FTTP Using Gigabit Passive Optical Network Architecture in Ghana - Isaac Adjaye Aboagye; Emmanuel Baah-Boadi; Jehkindra Klu-Jackson; Evans Danquah Boateng; Jesse Ghansah; Nii Longdon Sowah; Margaret Richardson Ansah (Journal of Engineering)
The main force behind the development of new access technologies is the rise in demand for high-speed internet. Also, the rapid expansion of digital services in Ghana has necessitated the deployment of high-speed broadband networks. Various technologies that use optical fiber as a transmission medium make up the fiber-to-the-premises (FTTP) family of technologies. In our research, we designed and implemented a gigabit passive optical network (GPON). This research provided a detailed design and field implementation of a secure FTTP access network supporting up to 128 clients. It focused on the design and implementation of FTTP using GPON architecture, which offers a cost-effective solution for delivering triple-play services (voice, data, and video) over fiber optic cables, providing high bandwidth and reliability. The GPON system consists of an optical line terminal (OLT) at the central office and optical network terminals (ONTs) at user premises, connected via passive optical splitters that distribute signals to multiple users. The fundamental elements of the network are discussed, along with how each element contributes to the FTTP network architecture. We designed a splitter configuration that divides an incident light beam from a single input fiber cable into eight different output cables, which is our first-level splitting. The architecture includes security features in the feeder network to provide redundancy. Each of the eight output fiber cables is divided into 16 separate output cables to provide network access to all 128-end clients. In doing so, we identify the optimal splitting ratio combination that will allow for quick data transmission and better performance to improve broadband services, support future-proof bandwidth demands, and contribute to the country’s technological advancement.